The influence of temperature on the electrical conductivity of GaN piezoelectric semiconductors - Qiao, Y.; Zhao, M.; Qin, G.; Lu, Chunsheng; Fan, C. (2023)
GaN is an excellent material choice for power devices due to its excellent properties such as super wide bandgap width and high electron mobility. However, the problem of temperature affects the thermo reliability and hinders the potential of GaN devices. In this paper, the electrical properties of GaN under temperature have been studied by the combination of numerical simulation and experimental research. The electric current change and electrical resistivity of polarized and depolarized GaN semiconductor samples were tested in an environment-test cabinet. Based on the influence of temperature, the expression of the resistivity curve vs temperature was established for polarized and depolarized GaN samples. It is shown that the resistivity model predictions are consistent with experimental results. The I-V characteristic curves under different temperatures were also measured. Thus, such a model is instructive to the reliable design of GaN high-temperature devices. The findings will be instructive to the optimal design of GaN electronic components.